2001
DOI: 10.1211/0022357011777891
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cannabinoid receptor agonists against cocaine and other convulsant-induced toxic behavioural symptoms

Abstract: Based on the previously reported co-localization and relationship between cannabinoid and dopamine receptors, the effects of cannabinoid receptor agonists against cocaine-induced toxic behavioural symptoms, including convulsive seizures, were examined in mice. The anticonvulsant effect of several cannabimimetics against seizures induced by other convulsants was also compared. The cannabinoid receptor agonists CP 55940 ((-)-cis-3-[2-hydroxy-4-(1,1-dimethylheptyl)phenyl]-trans-4-(3-hydroxypropyl)-cyclohexanol) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 45 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The mortality rate was also compared between the groups using Fisher's exact test (Matsumoto et al, 2001). For the seizure scores, the Mann-Whitney U test was performed after the data were subjected to a KruskalWallis analysis of variance (Sañudo-Peña et al, 2000;Hayase et al, 2001). All of the comparisons were performed using a statistical software package and its manual (OMS (2004) that some mitochondrial functions are activated by toxic convulsion-inducing drugs, including cocaine (Keys et al, 1998;Kunz, 2002), it is possible that these modifications in the expression of mitochondrial genes, despite the fact that their functions have not been elucidated, made some contributions to the toxic effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate was also compared between the groups using Fisher's exact test (Matsumoto et al, 2001). For the seizure scores, the Mann-Whitney U test was performed after the data were subjected to a KruskalWallis analysis of variance (Sañudo-Peña et al, 2000;Hayase et al, 2001). All of the comparisons were performed using a statistical software package and its manual (OMS (2004) that some mitochondrial functions are activated by toxic convulsion-inducing drugs, including cocaine (Keys et al, 1998;Kunz, 2002), it is possible that these modifications in the expression of mitochondrial genes, despite the fact that their functions have not been elucidated, made some contributions to the toxic effects of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, throughout the administration period, lethality (mortality rate) and convulsive seizures (seizure scores) were recorded as toxic behavioural signs. The severity of seizures after the last cocaine administration was scored following a previously reported method (Hayase et al, 2001): score 0 = no convulsive seizures; score 1 = short-lasting (<5 min) mild episodes of clonic convulsions; score 2 = episodic clonic convulsions accompanied by a loss of the righting reflex; score 3 = episodic convulsive seizures accompanied by continuous severe clonus or rearing; score 4 = episodic convulsive seizures, continuous and violent enough to cause fatal respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The final doses used caused convulsive seizures of a similar severity (based on the criteria by De Sarro [47] and Braida [48]) and death in a similar percentage of rats, under the present conditions, in a preliminary trial: 60 mg/kg for COC hydrochloride (Takeda Chemical Industries, Ltd., Osaka Japan), 5 mg/kg for BIC (Tocris Cookson Inc., Ballwin, MO, USA), 10 mg/kg for DMCM (Sigma-Aldrich, Inc., Saint Louis, MO, USA), and 200 mg/kg for NMDA (Nacalai Tesque, Inc., Kyoto, Japan). All of the convulsion-inducing drugs were administered by an intraperitoneal (IP) injection of a mixed dimethylsulfoxide (DMSO)-distilled water (1:2) solution in a volume of 5 ml/kg body weight [7]. The group of rats treated with a physiological stressor underwent 10 min of immobilization stress [26], which was induced by placing the rat in a narrow space (diameter 18 cm) made in a vinyl bag with some breathing holes (IM group).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is also possible that GABA receptor antagonists such as bicuculline (BIC), benzodiazepine receptor inverse agonists such as methyl 6,7-dimethoxy-4-ethyl-β-carboline-carboxylate (DMCM), and glutamate receptor agonists such as NMDA also function as stressors, because of their convulsion-inducing effects and the close correlation between their target receptors and the stress response [1-3]. Although these drugs, including COC, have different target receptors, previous studies on the convulsive profiles of each drug have reported no peculiar differences with respect to the induction of stress reactions [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The activation of presynaptic CB1 receptors that are present on GABAergic and glutamatergic interneurons through ECs, such as AEA, also appear to play a critical role in regulating inhibitory and excitatory neurotransmissions [68,69]. The AEA has been found to modulate the activity of NMDA receptor via non-CB1 receptor mediation [70] and has been shown to antagonize cocaine-induced lethality and NMDA-induced convulsive seizures [71]. The pretreatment with SR141716A abolishes anticonvulsant effect of AEA in an electroshock seizure model, indicating the modulation of seizure activity by AEA tone.…”
Section: Alcoholism and Endocannabinoid Systemmentioning
confidence: 99%